Manfaat Senyawa Eupatorin pada Tumbuhan Kumis Kucing sebagai Agen Antikanker melalui Mekanisme Penghambatan Proliferasi Sel - Nerdy Nerdy; Nilsya Febrika Zebua; Syadzna Malika Maimun; Miswati Furqani; Hafizatun Suardi; Nabila Aini; Shahira Yasmin; Winny Wastika Syahfitri (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to analyze the potential of eupatorin found in Cat’s Whiskers (Orthosiphon stamineus) as an anticancer agent using in silico methods. Eupatorin was selected due to its promising biological activity reported in previous literature. The research employed compound structure data registered in PubChem, analyzed through PASS Online for pharmacological activity prediction, ProTox-II for toxicity evaluation, and pkCSM for ADMET parameters. The results indicated that eupatorin has a high probability of inhibiting cancer cell proliferation with significant pharmacological activity values. Toxicity predictions showed a safe profile with an LD50 supporting its potential therapeutic use. ADMET analysis demonstrated that eupatorin possesses good bioavailability, adequate absorption and distribution, and minimal metabolic interactions, supporting its efficacy as an anticancer compound. These findings suggest that eupatorin could be an important candidate for herbalbased drug development, particularly for cancer therapy, and provide opportunities for further research through in vitro and in vivo experiments to validate anticancer activity comprehensively.